Understanding the needs of undergraduate healthcare students in relation to suicide prevention training: A qualitative study - Kerrie Gallagher; Ellen Walls; Clíodhna O’Brien; Eve Griffin; Grace Phillips; Michelle O’Driscoll (PLoS ONE, 2025)
Background International evidence indicates that many healthcare workers are not adequately prepared to support patients during suicidal crises. As a result, healthcare students need appropriate training in order to effectively intervene once they qualify. In Ireland, there is no standardised suicide prevention training for students who are undertaking a degree in the health professions. The aim of this study was to explore the perspectives of undergraduate healthcare students to inform the design, implementation and evaluation of a suicide prevention module. Methods Ethical approval was obtained to conduct focus groups with undergraduate healthcare students. Recruitment was by convenience and snowball sampling within the research team’s networks. Eligible participants for this study were students over the age of 18 who were enrolled in an undergraduate healthcare course. Focus groups were held online via MS Teams, and were subsequently transcribed and qualitatively analysed using Braun and Clarke’s thematic analysis. Results A total of 12 participants from Graduate Entry Medicine (n = 9) and Pharmacy (n = 3) took part across four focus groups, which averaged 53 minutes in duration. Six key themes emerged from the data: (i) the need for suicide prevention training for healthcare students; (ii) “tiptoeing” around the topic of suicide; (iii) creating a safe environment; (iv) student self-care and support – different strokes for different folks; (v) module implementation and (vi) appropriate teaching methodologies. Conclusions Healthcare students would positively receive the embedding of suicide prevention training into their respective degrees. The findings of this study serve to include the student voice in a suicide prevention curriculum design, and have since been used to inform its subsequent pilot and evaluation. This will ultimately improve the suicide prevention knowledge and competence of our future healthcare professionals.